A retrospective study on the prevalence of main clinical findings in brown bears (Ursus arctos) rescued from substandard husbandry conditions - Stagni, Elena; Sequeira, Sara; Brscic, Marta; Redtenbacher, Irene; Hartmann, Sabine (Frontiers in Veterinary Science, 2023)
Brown bears (Ursus arctos) are kept under varied captive conditions, some of which may greatly compromise their welfare. FOUR PAWS is an NGO that rescues some of these bears kept in substandard conditions and houses them in species-appropriate sanctuaries, where preventive and reactive veterinary care is provided. This retrospective study aims to provide an overview of pathologies and clinical abnormalities reported in veterinary records and their prevalence according to body system affected and pre-rescue bear origin. Origin was categorised as subzoo (bears coming from substandard zoos), dancing (used to “dance” upon music cue), restaurant (used to attract clients), private keeping (used for various purposes, such as photo props), circus (used for shows), and bear-baiting (exploited for hunting dog training, in baiting stations). Clinical findings were extracted from reports of veterinary examinations done from 2006 to 2021, during rescue, routinely, in response to clinical signs, and/or post-mortem. Their prevalence was calculated according to body system affected and neoplasia (specific group independent from the organ) over the findings’ total number. Prevalence was calculated also according to pre-rescue origin (general and relative values in proportion to number of reports per origin). Results refer to 302 veterinary reports of 114 bears examined, rescued from 1998 to 2021, with age at rescue varying from a few months to 30 years (median 13 years). The total number of clinical findings was 1003 and the systems with more findings were: oral cavity (56.0%), abdominal cavity and digestive system (7.9%), integumentary (7.9%), ocular systems (7.7%), and musculoskeletal (7.6%). Findings involving other body systems and neoplasia were less prevalent (≤2.8%). Results showed higher prevalence of some clinical findings for bears rescued from certain origins compared to others. Straightforward associations between pre-rescue origin and clinical finding were not feasible due to unknown anamnesis and details on pre-rescue conditions, and because some housing and management characteristics might be transversal to origins. Results suggest that bears rescued from certain origins were prone to specific clinical findings, supporting the need for the creation of ad hoc preventive veterinary and husbandry management plans after rescue, thus contributing to the improvement of captive bear welfare.